PEMANFAATAN REFLEKTOR UNTUK PENINGKATAN DAYA LUARAN PANEL SURYA - Nuha Nadhiroh; Dezetty Monika; Arum Kusuma Wardhany; Ajeng Bening Kusumaningtyas; Isdawimah *; Muchlishah * (Politeknik Negeri Jakarta, 2022)
The Government of Indonesia has committed to support the development of solar power plant, while the efficiency of solar panels still around 5-16%. There are several methods to increase the output power of solar panel, but mostly consume a big portion of energy from solar power plant. The objective is to identify an off-grid solar power plant optimization method with smaller power consumption. The proposed optimization method is to add a reflector that can be positioned to direct sunlight so that it always hits the solar panel, so that the solar panel is able to produce electrical power optimally. This method can save the use of electrical power, because the weight of the reflector is much lighter than solar panels. The position of the reflector can be adjusted automatically based on feedback from the monitoring system. Off Grid solar system consisting of solar panels, batteries, solar charge controller (SCC), inverters, safety against overloads, short circuits and lightning strikes and mounted reflectors that can be adjusted in position, so that a lot of sunlight hits the solar panels so that the solar panel output power increase. In choosing the type of reflector, several things need to be considered, namely weight, refractive index, size, shading effect and the reflector's resistance to wind, impact and shock. Data retrieval is carried out automatically with a monitoring system to measure and store data when testing solar power system without reflectors and with reflectors in various positions. Data retrieval is based on IEC Standard 61724, while data processing is based on IEA-PVPS T2-01, 2000. Installing reflectors on solar panels is proven to increase the output power of solar panels, where aluminum reflectors and flat mirrors produce the greatest output power at an angle of 83°. Flat mirror reflectors produce a greater increase in solar panel output power compared to flat aluminum reflectors